An overview of cognitive visualisation - Mooranian, Mahsa; Dillon, Tharam; Chang, Elizabeth (IEEE, 2011)
Since the beginning of mankind, there has been a need to display knowledge in such a way that it could be easily understood. In today’s highly technological world we face an overwhelming amount of information from a variety of sources, namely: business applications such as customer comments and communications, trade publications, internal research reports and competitor web sites. Most of this knowledge is stored in textual format so in order to conceptually visualize this information, we need to extract the knowledge it contains and then try to comprehend it. However, one of the characteristics of textual information is its unstructured format which is not readily assimilated and understood. This paper presents a summary of current techniques used in information visualization. We present some of the main visual text analytics systems, highlighting their techniques, in addition to providing a brief overview of visual text analytics, semantic analysis of text and ontology that could be used to facilitate the process of cognitive visualization.